Pricing and Liquidity of Complex and Structured Derivatives Deviation of a Risk Benchmark Based on Credit and Option Market Data - Schmidt, Mathias (SpringerBriefs in Finance, 2016)
XVII, 114 p. 32 illus., 16 illus. in color.